Proceedings of the 2014 IEEE 15th International Conference on Information Reuse and Integration (IEEE IRI 2014) 2014
DOI: 10.1109/iri.2014.7051954
|View full text |Cite
|
Sign up to set email alerts
|

A hidden treasure? Evaluating and extending latent methods for link-based classification

Abstract: Abstract-Many information tasks involve objects that are explicitly or implicitly connected in a network, such as webpages connected by hyperlinks or people linked by "friendships" in a social network. Research on link-based classification (LBC) has studied how to leverage these connections to improve classification accuracy. This research broadly falls into two groups. First, there are methods that use the original attributes and/or links of the network, via a link-aware supervised classifier or via a nonlear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In recent work [Fleming et al 2014;, we evaluate many of the methods described above, including those of Tang et al, Shi et al, and Lin and Cohen. Compared to RCI, RI, and CI, we found that some of the the latent methods can be competitive when the network is densely labeled or when the attributes are not very informative but that when the network is sparsely labeled, RCI and/or RI generally provide the best accuracy, with some significant gains vs. the latent methods.…”
Section: Related Workmentioning
confidence: 99%
“…In recent work [Fleming et al 2014;, we evaluate many of the methods described above, including those of Tang et al, Shi et al, and Lin and Cohen. Compared to RCI, RI, and CI, we found that some of the the latent methods can be competitive when the network is densely labeled or when the attributes are not very informative but that when the network is sparsely labeled, RCI and/or RI generally provide the best accuracy, with some significant gains vs. the latent methods.…”
Section: Related Workmentioning
confidence: 99%
“…An earlier version of this work was described by Fleming et al [5]. That earlier paper compared latent vs. non-latent methods and introduced the taxonomy of Section 6.…”
Section: Related Workmentioning
confidence: 99%